2022
DOI: 10.1136/archdischild-2022-324174
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic conditioning in necrotising enterocolitis: a phase I feasibility and safety study

Abstract: ObjectiveRemote ischaemic conditioning (RIC) improves the outcome of experimental necrotising enterocolitis (NEC) by preserving intestinal microcirculation. The feasibility and safety of RIC in preterm infants with NEC are unknown. The study aimed to assess the feasibility and safety of RIC in preterm infants with suspected or confirmed NEC.DesignPhase I non-randomised pilot study conducted in three steps: step A to determine the safe duration of limb ischaemia (up to 4 min); step B to assess the safety of 4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with preclinical rodent studies of stroke where RIC significantly reduced the extent of ischemia and neurological deficits (7). Furthermore, RIC was found to be safe and feasible in neonates of younger gestational age and lower birth weight (8). However, the effects of RIC on neonates with HIE undergoing TH has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with preclinical rodent studies of stroke where RIC significantly reduced the extent of ischemia and neurological deficits (7). Furthermore, RIC was found to be safe and feasible in neonates of younger gestational age and lower birth weight (8). However, the effects of RIC on neonates with HIE undergoing TH has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that this method is particularly effective and significantly reduces the extent and severity of bowel injury compared to controls ( 24 ). At this stage human studies have not progressed beyond safety studies but further clinical research is in progress included a feasibility randomised controlled trial ( 25 , 26 ). Human breast milk, either maternal or donor, has been shown to almost half the risk of NEC vs. formula feed in meta-analysis ( 27 ).…”
Section: Introductionmentioning
confidence: 99%